The Effect of Cash Flow and Profitability on Accounting Conservatism in Technology and Health Companies on the Indonesia Stock Exchange - Susi Susanti; Susi Retna Cahyaningtyas (International Journal of Business and Quality Research, 2024)
This study aims to analyze the effect of cash flow and profitability on accounting conservatism listed on the Indonesia Stock Exchange in 2018-2022. The type of data in this study uses quantitative data with the population being technology and health companies listed on the Indonesia Stock Exchange (IDX). The sample selection method used is purposive sampling so the total selected sample is 34 companies with observer data for the last five years, namely in the 2018-2022 period so that the total sample is 170 data. Data analysis in this study is panel data modeling with the EVIEWS 12 program. The results of this study found that Cash Flow and Profitability have a positive effect on Accounting Conservatism in technology and health companies listed on the Indonesia Stock Exchange.